Saponin Formosanin C-Induced Ferritinophagy and Ferroptosis in Human Hepatocellular Carcinoma Cells - Pin-Lun Lin; Han-Hsuan Tang; Shan-Ying Wu; Ning-Sing Shaw; Chun-Li Su (MDPI AG, 2020)
Ferroptosis, a recently discovered form of iron-dependent cell death, requires an increased level of lipid-reactive oxygen species (ROS). Ferritinophagy, a ferritin degradation pathway, depends on a selective autophagic cargo receptor (NCOA4). By screening various types of natural compounds, formosanin C (FC) was identified as a novel ferroptosis inducer, characterized by attenuations of FC-induced viability inhibition and lipid ROS formation in the presence of ferroptosis inhibitor. FC also induced autophagic flux, evidenced by preventing autophagic marker LC3-II degradation and increasing yellow LC3 puncta in tandem fluorescent-tagged LC3 (mRFP-GFP) reporter plasmid (ptfLC3) transfected cells when combined with autophagic flux inhibitor. It is noteworthy that FC-induced ferroptosis and autophagic flux were stronger in HepG2 cells expressing higher NCOA4 and lower ferritin heavy chain 1 (FTH1) levels, agreeing with the results of gene expression analysis using CTRP and PRISM, indicating that FTH1 expression level exhibited a significant negative correlation with the sensitivity of the cells to a ferroptosis inducer. Confocal and electron microscopy confirmed the pronounced involvement of ferritinophagy in FC-induced ferroptosis in the cells with elevated NCOA4. Since ferroptosis is a non-apoptotic form of cell death, our data suggest FC has chemotherapeutic potential against apoptosis-resistant HCC with a higher NCOA4 expression via ferritinophagy.